KARAKTERISTIK HIDRODINAMIKA ALIRAN AIR DISEKITAR PROPELLER-RUDDER PADA BERBAGAI BENTUK PROFILE RUDDER DAN JARAK DENGAN PROPELLER - Jihadin Ilmi Muhammad; Anis Mustaghfirin Muhammad; Santoso Emie (Proceedings Conference on Marine Engineering and its Application, 2018)
Maneuverlability on ship design should be resolve all resistance effect to get standard velocity of moving the ship. The caracteristic of the rudder-propeller is very important to the performance to manuver. Distance of the rudder-propeller (Hugo,2016), shape of rudder profile (Liu,2016), is very pengaruhnya jika mengunakan tipe twin screw (muscari,2017). In this case to know velocity countour around of propeller rudder on the perintis ship 2000GT with distance variation rudder to propeller and rudder profile variation. Our porpose is get the best drag and lift for better manuvering. We design on 3D model with PropCad for Propeller, Maxsurf for Hull and Spaceclaim for rudder and assembly all component. Our Analys should in CFD and the process use ANSYS FLUENT to show hydrodynamic characteristic, In this final project we use real validation from sea trial results. From this model we get velocity approtimate with sea trial results validation. In sea trial results the velocity is 9-13.3 knot or 4.63-6.842 m/s. Otherwise in ANSYS simulation show 4.18-8.37 m/s from velocity 1ounter in Fluent with rotation propeller 424 rpm in the real condition design. After this we know the best rudder NACA profile is NACA0018 and the best distance is 25% Propeller Diameter.